Cornered Islamic Society: A Critical Discourse Analysis on Islamophobic Memes - Rizky Anugrah Putra (Yayasan Visi Intan Permata, 2022)
In the era before the internet, memes could take the form of posters containing messages, invitations, and even propaganda. Propagandists manipulated those discourses and presented them at public events such as theatres and festivals. It has evolved into computational propaganda using media and popular memes in the modern era. Muslims are effortless targets for offensive memes, which have been going on for the last decade. This prejudice has become a familiar issue for internet users and vandalizes the image of Muslims and links Muslims to all social problems that transpire in society. This study examined Islamophobic theme memes transmitted on international memetic sites. Popular Islamophobic memes were analyzed using critical discourse analysis to break down the phenomenon based on visual, textual, and social motives. The findings demonstrated that the meme creators utilized the hottest issue to induce the ill idea of demonizing Muslim society and tend to alter the information in their favour. Memes with Islamophobia discourse often included provocative sentences that satirize the teachings of Islam accompanied by words that collocate with aspects of terror, terrorism, radical, extremism, violence, and abuse. That discourse influenced opinions and damaged the image of the target meme, and this method was remarkably efficacious, as evidenced by a large amount of support obtained on anonymous sites. In addition, this meme was distributed in anonymous forums, where this forum ensured the privacy of the meme's sender without worrying that his insults in cyberspace would affect the real world.